CHEMICAL COMPOSITION OF RADISH WASTES (PEEL AND LEAVES) AND THEIR HEALING PROPERTIES - Atakulova Nargiza Bakhtiyorjon qizi; Odilova Sarvinoz Burkhonjon qizi (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
This article presents information on the chemical composition of radish waste and its use in folk medicine.